Торговые пути и миграции в Юго-Восточной Европе в раннем бронзовом веке - Иванова, С.В. (Материалы по археологии Северного Причерноморья, 2010)
The end of 4000 B.C. – the beginning of 3000 B.C. saw the creation of the “salt way” that connected the north-west of the Black Sea steppes with the Carpathian Balkan region and the West Asia (Anatolia). It is the trading interest that caused the expansion of the Pit Grave Culture tribes to the Balkans and provided the further development of this region. Ancient population created the trading network that covered all the territory of the South-Eastern Europe. The network provided the flow of goods from the Carpathian Balkan region to the north-west of the Black Sea region and in the opposite direction. The ways from the north-west of the Black Sea region in the eastern (over the Southern Bug) and northern (up the Dniester stream) directions emerge. Salt extracted from local salt coastal lakes was the major export commodity. The major imports included copper and goods produced from it, silver jewelry and, possibly, food. Colonization had a trade nature and is characterized by development of peaceful relations with local population and appearance of syncretic monuments. Goods transport capable of conveying great amount of salt gave Pit Grave tribes the opportunity to launch long expeditions, the routes of which are marked by burial place of the elite (silver temporal pendants, carts). The role of the Pit Grave Culture for the steppe zone of the Black Sea region may be compared with the one that is peculiar to the bearers of the Baden Culture in the Central Europe and the Balkans: the spread of innovations, trade and colonization.